(untitled) (Bangladesh Journal of Psychiatry, 2022)
The older population is rapidly growing throughout the world. Bangladesh has a long cultural and religious tradition of looking after the elderly and it is expected that families and communities will care for their own elderly members. But rapid socioeconomic and demographic transitions, mass poverty, changing social and religious values, influence of western culture, and other factors have broken down the traditional extended family and community care system. Most of the elderly people in Bangladesh suffer from some basic human problems, such as poor financial support, senile diseases, and absence of proper health and medicine facilities, exclusion and negligence, deprivation, and socioeconomic insecurity. Increase care based on socio-demographic variation may be more able to improve the quality of life of elderly people as well as old care home residents. This cross-sectional study was done to find out the socio demographic variation among 138 elderly respondents irrespective of sex living two different old care homes of Bangladesh from January 2018 to September 2019. They were interviewed with a socio-demographic questionnaire. The results showed that, the mean age of the respondents was 70.83±8.28 years and more than half (54.35%) of the respondents were 60-69 years of old. The respondents were predominantly male (58.7%). with male to female ratio being roughly 3:2. More than half of the respondents (52.2%) were from urban background and rest (47.8%) were from rural background. Nearly three quarters (87.7%) of the respondents were Muslim and 8.7% were Hindus. More than 50% had monthly family income of <10000 Bangladeshi taka (BDT). Majorities (70.3%) of the respondents were widow/widower and 10.9% were single. Over one third (38.4%) of the respondents were studied up to primary level, 26.8% were graduated, 14.5% were studied up to secondary level and 11.6% up to higher secondary level. A few respondents were illiterate (8.7%). Most of them came from nuclear family (79.7%). and rests were from joint family (20.3%). It was seen that, single or widower urban male people from nuclear family were more coming in the old care home. Majority (60.9%) of the respondents had chronic physical illness. A few of the respondents had family history of mental illness (7.2%). Only 1.4% had history of drug addiction. The mean duration with standard deviation of staying in old care home by the respondents was 4.145±3.35 years. Bang J Psychiatry 2022;36(2): 35-38